SOCIO-LEGAL PERSPECTIVES ON THE OMNIBUS LAW IN THE ERA OF INDUSTRIAL REVOLUTION 4.0: A CASE STUDY OF BATAM CITY - Marbun, Djandel Dachlan Pangihutan; Nurlaily, Nurlaily; Shahrullah, Rina Shahriyani (Universitas Internasional Batam, 2023)
Industrial Revolution 4.0 (IR 4.0) has the potential to improve the quality of life for people around the world, but it also has caused the waves of unemployment and layoffs. The Indonesian government has set 10 national priorities to deal with the IR 4.0 by â€œharmonization of rules and policiesâ€ (Priority 10 of Making Indonesia 4.0). In this regard, the government adopts the Omnibus Law approach by enacting the Job Creation Law. This study aims to ascertain the perspectives of Batam people regarding the Job Creation Law whose status is still conditionally valid. This study adopts empirical legal research by collecting and processing 2 types of data, namely primary data and secondary data. Both data were analyzed by using a descriptive qualitative approach. It found and concluded that based on the survey of 210 workers in Batam City, they have positive perceptions of the Job Creation Law since they consider that the Law provides more legal certainty than the former Employment Law. They are also more favorable of this Law than the former Employment Law because it abolishes the overlapping regulations and make one new effective regulation to improve the economy of people. In addition to the Central Governmentâ€™s efforts to fulfil the requirements of the Constitutional Court Decision Number 91/PUU-XVIII/2020, various stakeholders in Batam City have contributed their insights and inputs to make the Job Creation Law perfect to respond many challenges in the era of RI 4.0. and it can be valid and fulfill the requirements of the Constitutional Courtâ€™s Decision.